ISOLATION OF UROPATHOGENS AND THEIR ANTIBIOTIC SUSCEPTIBILITY PATTERN AT A TERTIARY CARE HOSPITAL IN NORTHERN INDIA - HARIT KUMAR; VARSHA A SINGH; SHAVI NAGPAL; DIPANKAR BISWAS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to know the isolation rate and antibiotic susceptibility pattern of pathogens causing urinary tract infection (UTI). Methods: A total of 500 urine samples of clinically suspected UTI were collected from January 2019 to June 2019. The samples were inoculated on Cystine Lactose Electrolyte-Deficient agar and incubated at 37°C for 24 h. Results: In our study, 303 (60.6%) samples showed growth of isolates. Among 303 isolates, 31 were Candida spp. which was not included in the study. Out of 272 isolates, Escherichia coli was 31.68%, followed by Klebsiella spp. (27.72%), Enterococcus faecalis (22.44%), Citrobacter spp. (3.96%), Staphylococcus aureus (2.64%), and Pseudomonas spp. (1.32%). For Gram-negative and Gram-positive isolates, the most effective antibiotic was nitrofurantoin. Conclusion: The study shows E. coli as the predominant pathogen that causes UTI. Nitrofurantoin and fosfomycin showed very high susceptibility to uropathogens and can be used to treat primary or uncomplicated UTI.